Decomposição anaeróbia de Egeria densa Planch e Chara braunii Gmel em sistemas aquáticos sob diferentes estados tróficos - Barbosa, Vanessa Virginia (2015)
In this study there were three motivating questions: (i) are there differences in the decomposition kinetics of E. dense and C. braunii? (ii) in which trophic state the decomposition is faster? (iii) wthat is the magnitude of nutrients release in the water during decomposition? The hypothesis tested is that the decomposition kinetics is faster for C. braunii releasing few nutrients, because it is a seaweed, however, with both species faster decomposing in eutrophic water due to the greater microbial activity in the environment. Water samples were taken from eutrophic reservoirs with low nutrient content of the Paraiba semi-arid region. The in vitro study in which anaerobic conditions were analyzed: the decay of organic matter and release of nutrients during decomposition. Both species showed similar biphasic decay of organic matter and carbon mineralization and the trophic state did not influence this process. Nutrient release was high for both species, independent of the trophic state. The trophic state of Paraiba semi-arid water is not a limiting factor for the debry decay of E. dense and C. braunii. The species are from different families, but for being submerged macrophytes have similar content of plant fibers, as a consequence significant differences in weight loss was observed.